STRATEGI PENGEMBANGAN DESTINASI PARIWISATA BONTANG - Abdul Rachim; Reslianty Rachim; Muhammad Habibi; Zulkifli (University of Widya Gama Mahakam Samarinda, 2022)
Purpose and objectives Review tourism destination objects in Bontang City that can be developed with the aim of destination objects that can be developed for the advancement of the tourism industry. With the starting methodology, the preparation consists of forming groups, selecting themes and locations, as well directives for implementing activities. Finally, preparation is the stage that is carried out after the Fact Report and Analysis has been completed. The contents of the Plan Report include several points, namely Background, Purpose, Objectives, Policy Review, Overview of Study Areas, Tourist Destinations, and Tourism Development Policies and Strategies. As a result, the Bontang Kuala Village also has a mangrove conservation area in the form of the Dutch River. Bontang Tourist destinations in the Bontang Kuala and Bontang Lestari Villages have natural and cultural tourism attractions. Cultural Tourism in Bontang Kuala is located in the Tourism Village: Kampung Laut Bontang Kuala. Meanwhile, nature tourism in Bontang Kuala can be found in Bontang Mangrove Park TNK (Kutai National Park), Sungai Netherlands, and Segajah Island. As for cultural tourism in the Bontang Lestari Village, there is the Nyerakat Kampung. Natural tourism can be found in the Green Sustainable Valley, Lallo' Beach, Tihi-Tihi Village, Kadere Bay, Selangan Island, Beras Basah Island, Mangrove Park, Segajah Island, and traditional ceremonial activities. Those that can continue to be strategically planned to be developed as tourist destinations that become superior so that they can become the engine of the economy apart from LNG and Fertilizers. to be developed in the City of Bontang